Hubungan Riwayat Keluarga dan Aktivitas Fisik dengan Kejadian Hipertensi pada Ibu Hamil - Harmawati Rustan (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Hypertension in pregnant women is a serious health issue that contributes to the high maternal and fetal mortality rates. This condition can be influenced by various factors, including family history and physical activity. This study aims to analyze the relationship between family history and physical activity with the incidence of hypertension in pregnant women in the working area of Puskesmas Asera, North Konawe Regency. This research employs an observational analytic design with a case-control approach. The respondents consist of 38 pregnant women selected using the total sampling technique. Data were collected through questionnaires and medical records and then analyzed using the Chi-Square test. The results indicate a significant relationship between family history of hypertension (p=0.000) and physical activity (p=0.021) with the incidence of hypertension in pregnant women. This study concludes that hereditary factors and low physical activity increase the risk of hypertension during pregnancy. Therefore, preventive efforts are needed through health education, increased physical activity, and routine monitoring during pregnancy at healthcare facilities. With these measures, it is expected that the incidence of hypertension in pregnant women can be reduced, ensuring better maternal and fetal health.